Screening Winnie and African Feminist Herstories - Okech, Awino (Radical Teacher, 2021)
This teaching note offers reflections on the screening of Winnie an autobiographical documentary about the life of Winnie Mandela, South African liberation struggle actor. I explore the pedagogical decisions I made in screening this film which deals with the history of apartheid South Africa to a mixed audience at a university in London.